2009
DOI: 10.1007/s12011-009-8371-4
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Element Levels Indicating Exposure Profiles in Diabetic and Hypertensive Subjects from Mysore, India

Abstract: Element contents of teeth elucidate exposure nature, but less is known about association of tooth element concentrations of diabetics and hypertensives with exposure profile. Present study aims to estimate copper, chromium, iron, zinc, nickel, and lead concentrations in the permanent teeth of control, diabetic, and hypertensive subjects from Mysore. The results show that lead levels of teeth (Pb-T) are higher in the hypertensives and diabetics, whereas copper levels of teeth (Cu-T) are lower in the hypertensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The recent studies in adults showed that high PBT levels might be related with diabetes and hypertension [51]. It was also found that high blood lead (PBB) and PBH was associated with breast cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…The recent studies in adults showed that high PBT levels might be related with diabetes and hypertension [51]. It was also found that high blood lead (PBB) and PBH was associated with breast cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…These methods are commonly employed because the samples are easily collected. Tooth has also been used in one study [34]. The turnout rate of trace metals in the blood and urine is rapid; whereas the hair, fingernail and tooth accumulate these elements over a long period.…”
Section: Methods Commonly Employed To Assay Zinc and Copper In Human mentioning
confidence: 99%
“…Also, the effect of treatment time and the type of appliance used on the amount of released metal ions as a consequence of corrosion has not been evaluated. This is related with difficulties associated with the use of invasive vs. noninvasive biomarkers [13, 14]. It seems that multidisciplinary approach towards the problem of the assessment of exposure of human organism to trace elements may reveal different aspects associated with the application of metallic materials in dentistry [1518].…”
Section: Introductionmentioning
confidence: 99%